Protection of Human Rights in the Criminal Investigation Process: Special Reference to Suspects’ Right of Freedom from Torture in Sri Lanka - Liyanage, G.I.M. (My University, 2012)
The laws governing criminal procedure are based on a compromise between conflicting objectives of policy: on the one hand, effective law enforcement which concerns the security of the community as a whole and on the other, the protection of rights of the suspects. Criminal investigation is vested with the executive. And therefore the enforcement of the current criminal procedure in Sri Lanka is done by officers delegated with such powers. This has resulted in the creation of a tendency of exercising an excessive power during the investigation process. This tendency may get aggravated due to the nature of the criminal procedure adopted in Sri Lanka. According to the Article 7 of the ICCPR, no one shall be subjected to torture, to cruel, inhuman or degrading treatment or punishment. The Convention against Torture (CAT) strongly discusses the same rights. International instruments as well as the 1978 Sri Lankan Constitutions Section 11 have expressed the same. Despite this setting, we can still see police officers torturing suspects in order to obtain confessions. The extreme forms of torture used against suspected insurgents have become a habit within police stations and extreme forms of torture are used on persons suspected of petty theft, or even those arrested because of mistaken identity: some examples are Gerald Mervyn Perera case (SC.FR. App. No. 328/2002), the case of B.G. Chamila Bandara Jayaratne (SC. FR.App. No. 484/2003), case of Galappathy Guruge Gresha de Silva, Fr. Aba Costa case, and the case of Mulakandage Lasantha Jagath Kumara (SC. FR. App. No. 471/ 2000). In the case of Gerald Mervyn Perera, the suspected person was arrested because of mistake of identity. He was tortured to such an extent that within a few hours he suffered renal failure and had to be on a life support system for two weeks. Furthermore, there was serious damage to his arms due to hanging from the ceiling of the police station. Moreover, in the well-known case of the murder of 76 years Old Catholic priest Fr. Aba Costa, some suspects were arrested for murder, and within three days it was alleged that they were severely assaulted. Thereafter, they were charged with murder and remanded for a long time. Later on, once the actual criminals had reportedly been found, it was revealed that some senior police officers in the area were involved in the crime. Incidents of this nature happen in the process of Criminal Investigation. For these types of incidents Section 110 (2) of the Code of Criminal Procedure No.15 of 1979 is implicated by indicating police officers for torturing suspects. Therefore this study seeks to ascertain the nature in which suspects get tortured in the criminal investigation process by police officers and to suggest improvements to the laws relating to this area in order to minimize these types of violations and to protect rights of suspects.